Contemporary issues in mental health care in sub-Saharan Africa - Omigbodun, Olayinka, 1963-; Oyebode, Femi (Ibadan Medical Specialists Group, 2017)
Seventy percent of the global burden of mental disorders is located in low and middle income countries (LMIC),including sub-Saharan Africa (SSA). However, in Africa,only 0.62% of the national health budget is allocated to mental health compared to a global median of 2.8% and 5% in Europe. The government is the source of funding in 62%of patients with severe mental disorder in the World Health Organisation (WHO), Africa Region, the lowest of all the WHO regions, and lower compared to a global median of 79%. This is compounded by poor resources, with mental health outpatient facilities in WHO Africa Region being less that 10% of the global median. To address these problems, the WHO launched its Mental Health Action Gap Programme (mhGAP) in 2008, to scale-up mental health services in low and middle income countries (LMIC). The book is directed to all policy makers in sub-Saharan Africa to aid decision making about the urgent need for sustainable and relevant mental health care strategies, and the important areas that need priority. The book should be helpful to local and international researchers in formulating research questions relevant to the African continent and it will be of interest to medical practitioners and students in the region as adjunct to standard text books.